Synchronized chronology : rethinking Middle East antiquity : a simple correction to Egyptian chronology resolves the major problems in biblical and Greek archaeology - Henry, Roger, 1949- (Algora Pub., 2003)
Synchronized Chronology resolves the structural problems of Egyptian chronology and then outlines the correct history of the Middle East and Mediterranean from the time of Abraham and his wandering into the Empire of Alexander the Great. Recognizing some overlapping of dates and names in Manetho's List of Kings, frees history to place pharaohs and dynasties where archaeology supports their existence. This resolves a myriad of discrepancies and unlikely assumptions that historians have been forced to swallow, and neatly opens the way to synchronizing Egyptian dynasties with Biblical chronology. Several works have appeared in recent years, challenging Egyptian chronology; none is really successful in fixing the multi-layered problems of Biblical chronology, because they try to compress Egyptian history without recognizing duplicated dynasties. The crisis in Biblical history is reflected in The Bible Unearthed. Palestinian archaeologist William Dever has just published What Did the Biblical Writers Know, and When Did They Know It? Peter James received wide attention for his Centuries of Darkness; David Rohl, in Pharaohs and Kings, relies on the recent archaeological work of Beitak at Tel Dab'a in Egypt. The evidence is compelling that the site's population before the Hyksos took over was none other than the Hebrews. Rohl's work, on the period preceding the Exodus, is complementary to The Synchronized Chronology. Like James, however, he tries to squeeze the remaining Egyptian dynasties without discarding the duplicates. It doesn't work. Anyone who enjoys ancient history, archaeology or a good mystery will find this an intriguing read. The controversial theory is well-researched and sure to generate debate.